Expressing the level of curiosity of students studying in college - Hartini Hartini; Hendra Harmi; Fadila Fadila; Edi Wahyudi M; Jumira Warlizasusi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This research is designed to expose the level of curiosity of students in learning in the aspects of interest, novelty seeking, openness of experience, and exploration. In particular, we will measure the differences in curiosity assessed from the points of semester level and gender. The study involved 234 students in their third, fifth, and seventh semesters in nine study programs at the University. Data was collected from the curiosity questionnaire in learning, consisting of 48 items on the Likert scale with a reliability of 0.886. The results showed the level of curiosity of students in the aspects of interest, novelty seeking, and openness of experience to be in the medium category and in the exploration aspect, in the low category. On the other hand, students in the third semester a had higher curiosity in learning compared to students in semesters five and seven, while studies on the gender aspect did not find substantial differences in students' curiosity in learning.